Epidemiology of pulmonary embolism in China, 2021: a nationwide hospital-based study - Zhen, Kaiyuan; Tao, Yuzhi; Xia, Lei; Wang, Shengfeng; Gao, Qian; Wang, Dingyi; Chen, Zhaofei; Meng, Xianglong; Kang, Yuting; Fan, Guohui; Zhang, Zhu; Yang, Peiran; et al. (The lancet. Regional Health. Western Pacific, 2025)
Background - Pulmonary embolism (PE) as a preventable and potentially fatal noncommunicable disease was believed to have a lower incidence in Asian populations compared to Western populations. However, the incidence and mortality rates of PE in China and the impact of venous thromboembolism (VTE) prevention system constructions on PE still lack nationwide evidence. - Methods - For this nationwide hospital-based observational study, we used data from the National Hospital Quality Monitoring System (HQMS) and public database in China. We estimated the incidence and in-hospital mortality rates of PE by age group, sex, and regions of geographical and socioeconomic level. VTE prevention and management system constructions were quantified by geographical density. We then calculated the incidence and mortality rates in different conditions of VTE prevention and management system construction. - Findings - During the 12 months period between January and December 2021, a total number of 200,112 PE patients and 14,123 deaths were recorded from 5101 hospitals in the HQMS database. The incidence of PE was 14.19 (200,112, 95% CI 14.13-14.26) per 100,000 population and the mortality rate was 1.00 (95% CI 0.99-1.02) per 100,000 population. The incidence of PE was higher in male patients (14.43 per 100,000 population) than in female patients (13.95 per 100,000 population). Disparities of incidence and mortality rates were shown within age groups and geographical regions. The incidence and mortality rates of PE showed decreasing trend with increasing geographical density of VTE-related facilities and VTE prevention system developments. - Interpretation - China had a substantially large number of PE patients. The incidence and mortality rates of PE showed disparities in terms of sex, age, and geography. The incidence and mortality rates of PE decrease across regions with increasing levels of socioeconomic development, potentially influenced by the existing VTE prevention and management systems. Optimizing the health policies and healthcare investment in VTE prevention may help reduce the disease burden of PE. - Funding - CAMS Innovation Fund for Medical Sciences (CIFMS) (2023-I2M-A-014); National High Level Hospital Clinical Research Funding (2022-NHLHCRF-LX-01-0108); National Key Research and Development Program of China (2023YFC2507200); Discipline-Innovation and Talent-Introduction Program for Colleges and Universities (111 Plan, B23038).
Online verfügbar: 13. Dezember 2024
Gesehen am 05.08.2025